Features of the Bioconversion of Pentacyclic Triterpenoid Oleanolic Acid Using Rhodococcus Actinobacteria - Luchnikova, Natalia A.; Maltseva, Polina Yu.; Grishko, Victoria V.; Ivshina, Irina B. (KnE Life Sciences, 2022)
The ability of actinobacteria of the genus Rhodococcus to transform oleanolic acid (OA), a plant pentacyclic triterpenoid, was shown for the first time using bioresources of the Regional Specialized Collection of AlkanotrophicMicroorganisms (IEGM; WDCM #768;www.iegmcol.ru). The most promising strains (R.opacus IEGM 488 and R.rhodochrousIEGM 285) were selected, and these catalyzed80% bioconversion of OA (0.5 g/L) in the presence of n-hexadecane (0.1% v/v) for seven days. The process of OA bioconversion was accompanied by a gradual decrease in the culture medium pH. Adaptive responses of bacterial cells to the OA effects included the formation of compact cellular aggregates, a marked change in the surface-to-volume ratio of cells, and a significant increase in the Zeta potential values. The results demonstrated that the process of OA bioconversion was catalyzed by membrane-bound enzyme complexes. Participation of cytochrome P450-dependent monooxygenases in the oxidation of the OA moleculewas confirmedusing specific inhibitors. The obtained data expand our knowledge on the catalytic activity of actinobacteria of the genus Rhodococcus and their possible use as biocatalysts for the bioconversion of complex hydrophobic compounds. The results can also be used inthe searchfor promising OA derivatives to be used in the synthesis of biologically active agents. Keywords: bioconversion, oleanolic acid, Rhodococcus, biologically active compounds